Current status and applications of photovoltaic technology in wearable sensors: a review - Niranjan, D. B; Jacob, Jennifer; Vaidehi, B. R; Peter, Mathew; Medikonda, Jeevan; K. Namboothiri, Pramod (Frontiers in Nanotechnology, 2023)
The rapid development of wearable sensor technology can be attributed to developments in materials, microelectronics, fabrication, communication systems, and Artificial Intelligence (AI). The use of wearable sensors enables continuous acquisition and monitoring of the pathophysiological parameters of a person in real time. The global market for health-related wearables has experienced significant growth, particularly in response to the Covid-19 pandemic. A wearable sensor module is comprised of various components, including a powering unit, sensor(s), acquisition unit, communication unit, and processing unit. The non-fluctuating power source with a long life is of utmost significance to the continuous and real-time operation of a wearable sensor. A wearable device can be powered by a rechargeable battery, such as a lithium-ion battery, which can be charged from a standard power source but requires regular recharging after depletion and has a negative environmental impact. This necessitates using green renewable energy sources like photovoltaic cells, piezoelectric generators, wind energy converters, and thermoelectric generators for powering wearable sensor modules. The photovoltaic cell that converts photonics into electrical energy is deemed a viable green energy source for wearable sensor modules. This article reviews the progress and application of photovoltaic technology in wearable sensor modules.